Ensaios sobre o comportamento do mercado brasileiro de carne bovina - Albuquerque, Eucinete de Menezes (2023)
Brazilian beef cattle raising is becoming increasingly competitive, leading the country to occupy the second position as a producer and the world's largest exporter of beef. In this way, it is relevant to analyze the behavior of the price of live cattle, as well as the factors that influence it, as such an understanding helps in the strategic planning and decision-making of the stakeholders in this sector. Based on this argument, the set of studies now being reported examines, with care, three cases in the Brazilian beef market, using time series indicators of the prices of 12 Federative Units (FUs) in the period 2004-2021. In the first essay, price convergence is studied, using Phillips and Sul's (2007) time series analysis methodology. The results showed that prices are converging to a certain common level, that is, the beef market in Brazil denotes a global convergence, showing solid integration between markets. In the immediately following study, the cycles of price behavior in the main national bovine markets are examined. The consequences of this examination demonstrate that Brazilian cattle market cycles have asymmetric characteristics in terms of duration and intensity, as well as a certain level of synchronization between them. In the third experiment, the existence of structural breaks in the live cattle price series of the main Brazilian markets was investigated, using the methodology developed by Ditzen et al. (2021), based on Bai and Perron (1998, 2003). Derived from the effective investigation, five structural breaks emerged, suggesting that the effects of certain historical events, including government interventions, are likely to be related to changes in the price of beef in the country.